2018
DOI: 10.1177/0031512518774461
|View full text |Cite
|
Sign up to set email alerts
|

Self-Selected Training Load and RPE During Resistance and Aerobic Training Among Recreational Exercisers

Abstract: This study compared training load and ratings of perceived exertion (RPE) during resistance training (RT) and aerobic training (AT) sessions at self-selected intensity. Participants were 54 recreationally trained subjects assigned to either RT or AT groups. During RT, participants performed three sets of 10 repetitions of each exercise at a self-selected intensity (load). After RT completion, participants performed one repetition maximum (1RM) and 10RM tests. During AT, participants performed a treadmill exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…There are benefits with using subjective measures, such as low cost, efficiency, and not requiring a maximum strength test for prescription (Greig et al 2020). However, self-selected loads could be sub-optimal, as exercises have been suggested to be significantly underloaded (Dias et al 2018). The balance between ease of application and athletic benefits should be considered, as training time may limit opportunities for physical development and methods need to be effective.…”
Section: Resistance Trainingmentioning
confidence: 99%
“…There are benefits with using subjective measures, such as low cost, efficiency, and not requiring a maximum strength test for prescription (Greig et al 2020). However, self-selected loads could be sub-optimal, as exercises have been suggested to be significantly underloaded (Dias et al 2018). The balance between ease of application and athletic benefits should be considered, as training time may limit opportunities for physical development and methods need to be effective.…”
Section: Resistance Trainingmentioning
confidence: 99%
“…Although exercise intensity was prescribed via rating of perceived exertion, it was up to the participants to actually achieve this intensity and there is a possibility that exercises were done at other intensities ( Kilpatrick et al, 2020 ). Evidence exists that self-selected exercise intensity is often below the recommended one ( Focht, 2007 ; Elsangedy et al, 2013 ; Dias et al, 2018 ). Notably, recent studies dealing with unsupervised technology-based programs have faced similar challenges, with chair-rise tests producing promising but not significant results ( Yerrakalva et al, 2019 ; Van den Helder et al, 2020 ; Geraedts et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In studies with resistance-trained people (at least 12 months of experience with weight training), the self-selected loads were lower than those recommended for eliciting strength gains. [17,20] These studies consisted of only 1 experimental session. In the study of Faries and Lutz [28] that lasted 6 weeks, the authors observed that in the fifth training session, the loads reached those recommended by the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 5 years, several studies have been published testing this strategy in weight training. [17–21] In studies with sedentary elderly, it was observed that they self-selected intensities according to the last guidelines. [18,21] In a study by Elsangedy et al, [19] sedentary male subjects selected intensities above the intensity suggested to increase their strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation